Pengaruh Kualitas Pelayanan,Persepsi Harga Dan Atmosphere Terhadap Kepuasan Pelanggan - Klau, Clarita Merciani; Wasino, Hadi (Catalist Indo Publisher, 2025)
This study aims to analyze the effect of service quality, price perception, and atmosphere on customer satisfaction at Sugarbell bakery. The method used is a quantitative descriptive approach with data collection techniques through questionnaires distributed to customers who have made purchases at Sugarbell. The number of respondents in this study was 92 people. The data collected was then analyzed using multiple linear regression with the help of SPSS software version 25. The results of the analysis show that the variables of service quality and atmosphere have a significant effect on customer satisfaction. Meanwhile, price perception does not show a significant effect on the level of satisfaction. This indicates that non-price factors, such as the services provided and the atmosphere of the place, have a more dominant role in shaping customer satisfaction at Sugarbell bakery. Therefore, management is advised to continue to improve service quality and create a comfortable atmosphere in order to maintain and increase customer satisfaction.